Pengaruh Motivasi dalam Meningkatkan Kinerja Karyawan di PT. Sarana Tani Pratama Jembrana, Bali - Hajratul Aswah; Karma Karma; Abdullah Abdullah (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to determine the effect of motivation in improving the quality of employee performance at PT. Sarana Tani Pratama, a company engaged in fish canning, fish flouring, fish oil and cold storage. This research was conducted to explore the extent to which motivation can influence employee performance, in this case the fish canning industry. The background of this research is based on human resources which is one of the factors that greatly influences the level of performance quality. This research method uses a quantitative approach with data collection techniques using a questionnaire whose reliability and validity have been tested. The sample in this study consisted of 20 respondents.